Moral Self-Licensing and the Direct Touch Effect - Markus Sass; Joachim Weimann (Center for Economic Studies and ifo Institute (CESifo), 2015)
Repeated experiments with a time span of one week between repetitions are used in order to test two related hypotheses. The first is the moral self-licensing effect, which describes peo-ple's tendency to allow themselves to act more selfishly on the back of previous prosocial or selfless behavior. The second is the direct touch effect, which describes the difference be-tween experiences perceived directly by the senses and those perceived in a more hypothetical or abstract way. As games in which both effects can be detected we use the standard trust game and the mutual gift-giving game. Preferences were elicited by the strategy method and both games were played with and without feedback information between the waves. In both games, the moral self-licensing effect as well as the direct touch effect could be observed. Fi-nally, we use a solidarity game to check whether these effects also determine behavior in situ-ations with a different social norm. We find that this is not the case.
Keywords: C91; C73; 330; trust game; moral self-licensing effect; direct touch effect